A flat lens with tunable phase gradient by using random access reconfigurable metamaterial - Zhu, Weiming (2015)
The first demonstration of an optofluidic metamaterial is reported where resonant properties of every individual metamolecule can be continuously tuned at will using microfluidic system. This is called a random access reconfigurable metamaterial, which is used to provide the first demonstration of a tunable flat lens with wavefronts reshaping capabilities.